The relative effectiveness of the programed book and the workbook as enrichment materials for capable students - Del Mundo, Maria Luisa (Animo Repository, 1968)
This study investigated the difference between the mathematical achievement, as measured by the means of test scores, of two groups of capable high school students. Thirty-one pairs of first year high school students with the highest IQ and grades in mathematics were selected from all the six sections of the first year class in one RVM rural school. These pairs were matched on socio-economic background, sex, and IQ. The test for matched pairs, using the data on the thirty-one matched pairs, showed the achievement of the group that had used the programed book to be significantly greater (.01 level) than that of the group that had used the workbook as enrichment material. It was concluded that for first year high school capable students in RVM rural schools, the programed book used was more effective as enrichment materials than the workbook.